Network Pharmacology Analysis of the Mechanisms Underlying the Therapeutic Effects of Yangjing Zhongyu Tang on Thin Endometrium - Zhang L; Li H; Zhang L; Zu Z; Xu D; Zhang J (Dove Medical Press, 2023)
Lei Zhang,1,* Honglin Li,1,* Liang Zhang,2 Zhihui Zu,1 Dinglin Xu,1 Jianwei Zhang1,2 1The First Clinical College, Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 2Gynecology, Obstetrics and Reproductive Center, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianwei Zhang, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, 42, Wenhua West Road, Jinan, Shandong Province, People's Republic of China, Tel +8653168901404, Email zhangjianwei1970@sina.comPurpose: Yangjing Zhongyu Tang (YJZYT) is a classic Chinese prescription for infertility treatment and exerts therapeutic effects via activity on the thin endometrium (TE). However, the major components and underlying mechanisms of YJZYT actions remain to be established. The main objectives of this study were to clarify the effects of YJZYT on the TE and provide insights into the related mechanisms based on network pharmacology and molecular docking analyses.Methods: Network pharmacology was employed to explore the main bioactive components and targets of YJZYT. TE-related genes were obtained from the Genecards database and screened for intersections with YJZYT. The Cytoscape 3.8.2 was used to build a "compounds-disease-targets" network and molecular docking analysis performed on key targets. The mechanism of action of YJZYT was further validated in vivo using a rat model.Results: A total of 98 YJZYT active ingredients, 2409 thin endometrium-associated genes, and 186 common targets were obtained. Through topological analysis, 10 core objectives were screened. Data from the PPI network suggest that AKT1, TNF, VEGFA, IL-6, TP53, INS, ESR1, MMP9, ALB, and ACTB serve as key targets in the action of YJZYT on TE. PI3K-Akt, TNF, apoptosis, IL-17 and MAPK were established as the main functional pathways. Molecular docking analysis revealed high affinity of the active ingredients of YJZYT, specifically, ursolic acid, palbinone, stigmasterol, and beta-sitosterol, for TNF, VEGFA, IL-6, AKT, and MMP9. YJZYT improved endometrial recovery, promoted endometrial angiogenesis, and upregulated protein expression of VEGF, PI3K, AKT, and p-AKT in the TE rat model.Conclusion: Network pharmacological and animal studies facilitated the prediction and validation of the active components and key targets of YJZYT potentially contributing to TE. Preliminary evidence from in vivo experiments showed that YJZYT promotes angiogenesis and thin endometrial repair via regulation of the PI3K/AKT pathway, providing a reference for further research.Keywords: network pharmacology, molecular docking, Yangjing Zhongyu Tang, thin endometrium, PI3K/AKT signaling pathway